"A world for women": Fictions of the female artist in English-Canadian periodicals, 1840-1880. - Guth, Gwendolyn. (University of Ottawa (Canada), 1999)
Positioned somewhere between literary history and gynocriticism, this thesis proposes. a new way of viewing the years 1840--1880, the forty-year period that the Literary History of Canada charts as a steady, decisive, and necessary movement away from "a world for women"---away, in other words, from early, woman-tainted periodicals like The Literary Garland and toward the incipient "serious fiction" of the yet-unborn Week, itself prefigured by the establishment of the all-male Royal Society of Canada in 1882. By reclaiming instead of ridiculing, and validating instead of devaluing, this study overturns the patriarchal impulse of the Modernist epiteme, advocating instead a gynocentric appreciation of women whose contribution to nineteenth-century Canadian periodical writing cannot be overlooked, either statistically or qualitatively. Towards this goal, the dissertation raises up woman-authored fictions of the female artist figure---female Kunstlerromane---as a viable and revelatory genre of women's writing in nineteenth-century Canada. The topos of the female artist emerges, in the course of four chapters, as a self-consciously fraught site in which tensions of literary agency and critical reception struggle both inside and outside the particular historical moment of an individual work's publication. An introductory section focuses on various interpenetrations of gender and genre, mapping critical responses to the Bildungsroman and Kunstlerroman according to both non-feminist and feminist paradigms and assumptions, and noting the limited attention paid to Canadian texts in these genres. Chapter two outlines how the earliest woman-authored artist fictions published in Canada concerned male rather than female artists, yet worked subversively within a male paradigm. Of interest in this regard are several serialized stories from the 1840s and '50s by Eliza Lanesford Cushing (in The Literary Garland), Mary Eliza Herbert (in her own editorial venture, The Mayflower; or Ladies Acadian Newspaper), and two anonymous---and likely female-authors (in The Mayflower and The Anglo-American Magazine). Chapter three shifts the usual critical focus from Susanna Moodie's Roughing It in the Bush to her little-known serialized novel, "Rachel Wilde; or, Trifles from the Burthen of a Life" (1848). By viewing Moodie in her roles as both writer and editor of The Victoria Magazine, the venue in which "Rachel Wilde" appeared, the chapter explores her polemicization of the embryonic growth of a female artist. Chapter four recuperates Louisa Murray's contribution to post-Confederation Canadian literature by means of her serialized novel "Marguerite Kneller: Artist and Woman," published in 1872 in the first volume of The Canadian Monthly and National Review. By proposing a gendered aesthetics of compromise, and by taking issue, intertextually, with the British literary tradition, this work uncovers the extent to which Murray continued and augmented the literary "sorority" that earlier women like Cushing, Herbert, and Moodie had helped to foster. As writers, as editors, and as creators of a kind of representatively autobiographical agency in their fictions of the female artist, such women made valuable contributions to the heterogeneous project that would become increasingly defined, in the later nineteenth century, as "Canadian literature." The Literary History's damning epithet, "a world for women," thus becomes reconstituted, in the course of this thesis, as a more accurate critical insight. Which is to say, ironically but justifiably much of the world of nineteenth-century periodical fiction in Canada can indeed be considered "a world for women."
Keywords: Literature, Canadian (English).